The Experimental Area of Warthegau. Glossy to Some Statements of Edith Stein - Grzywacz, Małgorzata (Zeszyty Naukowe Centrum Badań im. Edyty Stein, 2016)
On the basis of fragments selected from the letters written by Edith Stain, an attempt was made to analyse her life in the context of the situation of the Jews in Germany in 1933-1942. The emphasis is put on the preparatory phase of the Nazi conception of Endlösung and on the role of the so-called Warta River Country (Warthegau) in the realisation of this conception. The history of the organisation of the first death camp for the Jews in Chełmno upon Ner is described.